Zirkulations- und Persistenzänderungen des europäischen Wettergeschehens im Spiegel der Grosswetterlagenstatistik - Klaus, Dieter (ERDKUNDE, 1993)
Changes in the frequency and persistence of European weather types for the period 1881-1991 are defined and causally explained. Since the late-sixties the values for frequency, but especially those for persistence, of large-scale weather situations with southerly flows over Germany have seen a significant increase, whilst there has been an equally significant decrease for those with northerly flows. This development, unprecedented in the past, coincides with increasing temperatures in the southern hemisphere compared to those in the northern hemisphere, a process which can be plausibly explained by the man-made greenhouse effect, by natural and anthropogenic aerosol loads in the atmosphere, and by the unusual variations in solar activity during the past two decades.